(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article focuses on developing listening skills at the B2 level goes beyond just listening to audio materials; it’s about actively engaging with the content and using strategies that help make sense of it. Although listening is crucial for communication, it is often overlooked in English teaching. It also explores interactive methods that are designed for B2 learners, focusing on group activities, multimedia tools, and task-based learning. By combining insights from both international research and Uzbek scholars, the study shows that using interactive techniques not only boosts listening comprehension but also encourages students to stay motivated and take charge of their own learning, especially when tailored to the needs of the classroom.